Application of ANP Network Analysis Process Method in SWOT Model - Fardin Nezafati Namin; Hamid Rez Askari; Sirous Ramesh; Seyed Masoud Mousavi Hassani; Esmat Khanmohammadi; Heydar Ebrahimi (Civil Engineering Journal, 2019)
Strategy is a comprehensive program for an action which defines the major directions of an organization and provides guidelines for resources allocation on the course to achieve the long-term goals of the organization. Choosing the right strategy is a complex and even risky task. This is because each strategy leads the organization to a specific competitive environment and determines how managers plan to match the strengths and weaknesses of an organization with the environmental opportunities and threats. SWOT analysis alone does not provide an analytical tool for recognizing the importance of identified factors and evaluating various strategic options based on the factors. For this reason, SWOT analysis has some deficiencies and shortcomings in the measurement and evaluation of the factors. Although the Analytical Hierarchy Process (AHP) can overcome these deficiencies, when there is a lack of independency and dependency between factors, the approach loses its efficiency. This is due to the fact that AHP assumes the possibility of factors involved in an independent hierarchy of structure if this assumption cannot be accepted for examining the effects of the internal and external environment. Therefore, a tool to consider and assess the possible dependencies among the factors has been needed. In this paper, an algorithm is presented based on the network analysis process, which can work well even when there is a dependency between the SWOT factors. Then, the green space conditions in Tehran's district 19 are analyzed by SWOT analysis where this algorithm is considered as a real case.